Efficacy of Low-Dose Corticosteroid Therapy Versus High-Dose Corticosteroid Therapy in Bell's Palsy in Children. (January 2017) - Arican, Pinar; Dundar, Nihal Olgac; Gencpinar, Pinar; Cavusoglu, Dilek
Bell's palsy is the most common cause of acute peripheral facial nerve paralysis, but the optimal dose of corticosteroids in pediatric patients is still unclear. This retrospective study aimed to evaluate the efficacy of low-dose corticosteroid therapy compared with high-dose corticosteroid therapy in children with Bell's palsy. Patients were divided into 2 groups based on the dose of oral prednisolone regimen initiated. The severity of idiopathic facial nerve paralysis was graded according to the House-Brackmann Grading Scale. The patients were re-assessed in terms of recovery rate at the first, third, and sixth months of treatment. There was no significant difference in complete recovery between the 2 groups after 1, 3, and 6 months of treatment. In our study, we concluded that even at a dose of 1 mg/kg/d, oral prednisolone was highly effective in the treatment of Bell's palsy in children.